Energetic Charged Particle Measurements During Juno's Two Close Io Flybys - C. Paranicas; B. H. Mauk; G. Clark; P. Kollmann; Q. Nénon; R. W. Ebert; J. R. Szalay; A. H. Sulaiman; J. E. P. Connerney; S. Bolton (Geophysical Research Letters)
Abstract On days 2023‐364 and 2024‐034, the Juno spacecraft made close passages of Jupiter's moon Io, at altitudes of about 1,500 km. Data obtained from the first flyby, when the spacecraft was on magnetic field lines connected to both Jupiter and Io, revealed deep flux decreases. In addition, Juno's energetic particle detectors observed tens to hundreds of keV electron and proton beams. Such beams could be generated near Jupiter on field lines associated with Io. The second encounter occurred in the plasma wake and a more modest flux decrease was observed. Furthermore, data from both encounters suggest a spatially extensive decrease in >1 MeV electrons that includes regions inward of Io's orbit. In the immediate vicinity of Io, signatures of absorption likely dominate the data whereas diffusion and wave‐particle interactions are expected to be needed to understand MeV electron data in the wider spatial region around Io.